Absorption of light by a particulate monolayer: Effect of ordering, concentration, and size of particles. (May 2019) - Miskevich, Alexander A.; Loiko, Natalia A.; Loiko, Valery A.
Highlights: Highly ordered c-Si-particle monolayer absorbs more light than partially ordered one. Order induced resonances can lead to more than 30-fold growing of light absorption. High order leads to 10-fold growing of light absorption at low-index region of c-Si. Abstract: Absorption of light by a free standing monolayer of monodisperse crystalline silicon (c-Si) spherical particles is investigated using the quasicrystalline approximation (QCA) of the theory of multiple scattering of waves. The simulation results for the partially ordered monolayer and the highly ordered monolayer with imperfect triangular lattice are presented in the ranges of particle diameters from 0.05 µm to 1 µm, monolayer filling factors from 0.1 to 0.7, and wavelengths of incident light from 0.3 µm to 1.12 µm. The spatial pattern of a monolayer affects the absorption coefficient most strongly when the particle sizes are comparable with the wavelength. The spatial-order-induced peaks in the absorption spectra of a highly ordered monolayer are studied. The spectral absorption by such a monolayer can be more than 30 times greater than that of the partially ordered monolayer in the narrow wavelength intervals. The integrated over the terrestrial solar spectral irradiance "Global tilt" ASTMG173-03 absorption coefficient is analyzed. In the wavelength range of 0.3 µm ≤  λ  ≤ 1.12 µm the integral absorption can be almost twice as large as that for the partially ordered monolayer. In the wavelength range of small absorption index of c-Si (0.8 µm ≤  λ  ≤ 1.12 µm) the integral absorption coefficient of highly ordered monolayer can be more than 10 times greater than for the partially ordered monolayer.